2011
DOI: 10.1158/1078-0432.ccr-11-0199
|View full text |Cite
|
Sign up to set email alerts
|

Development of Autoantibody Signatures as Biomarkers for Early Detection of Colorectal Carcinoma

Abstract: Purpose: To select autoantibody signatures for early detection of colorectal cancer (CRC). Experimental Design: A phage cDNA expression library was constructed with fresh tumors from 30 CRC patients and biopanned by using serum pools of 20 CRC patients and 20 healthy controls. A classifier was discovered in the training set of 30 CRC patients at stages I and II and 30 matched healthy controls and then blindly validated in an independent set of 60 CRC patients, 60 healthy controls, 52 polyps patients, and 30 au… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…In patients with earlystage NPC, use of the autoantibody panel provided a better diagnostic efficacy (Table 3). This indicates that the autoantibody panel may be a promising marker for the early detection of NPC and that the induction of autoantibodies occurs early in the process of carcinogenesis, which is consistent with previous studies (9)(10)(11)(12)(13)(14)(15)(16)(17). Analysis of VCA-IgA presented here is also shown to be a useful diagnostic biomarker of NPC, which is in agreement with a study by Ai and colleagues (21), but the high false-negative rates will prevent the timely diagnosis of NPC patients in endemic areas, particularly the symptomless, early-stage patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In patients with earlystage NPC, use of the autoantibody panel provided a better diagnostic efficacy (Table 3). This indicates that the autoantibody panel may be a promising marker for the early detection of NPC and that the induction of autoantibodies occurs early in the process of carcinogenesis, which is consistent with previous studies (9)(10)(11)(12)(13)(14)(15)(16)(17). Analysis of VCA-IgA presented here is also shown to be a useful diagnostic biomarker of NPC, which is in agreement with a study by Ai and colleagues (21), but the high false-negative rates will prevent the timely diagnosis of NPC patients in endemic areas, particularly the symptomless, early-stage patients.…”
Section: Discussionsupporting
confidence: 91%
“…Autoantibodies have attracted more attention as possible biomarkers in recent years. A large number of studies describe the presence of autoantibodies to tumorassociated antigens (TAA) in serum samples from patients with a variety of cancers (9)(10)(11)(12)(13)(14)(15). Interestingly, autoantibodies seem to appear months to years before the clinical diagnosis of a tumor, which makes measurement of autoantibodies suitable for earlystage cancer diagnosis (9,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the immune system of patients with cancers actively monitors and elicits T-cell and autoantibodies against tumor-associated antigens [26,27]. Some studies have demonstrated the appearance of serum autoantibodies as biomarkers for early diagnosis of human cancers [28][29][30]. Together, these clinical analyses clearly suggested that WAVE1 protein expression is a novel independent prognostic factor and biomarker of unfavorable outcomes from EOC.…”
Section: Discussionmentioning
confidence: 99%
“…Dieser Nachteil lässt einen Screeningeinsatz als noch nicht erfolgversprechend erscheinen. Er konnte jedoch in einigen Arbeiten durch die Bildung von Kombinations-Panels teilweise wettgemacht werden [21][22][23].…”
Section: Entwicklung Möglicher Tumormarkerunclassified